Dermatoglyphics As A Forensic Tool In Identification -A Survey Study - M. Subaraman, Dr. Abirami Arthanari (Drugs and Cell Therapies in Hematology, 2021)
Introduction Forensic Dermatoglyphics, one of the widely used branches, is basically the study and art of surface markings of skin, especially hands and feet. It is the configuration of the dermal ridge in palms, soles, and digits. The palms of the hands and the soles of the feet are covered with unique classes of marks. Scientifically, palmistry is now called dermatoglyphics. At the end of the 19th century, Galton put forth a rule called “proof of no change,” which reported that the dermatoglyphics pattern remains unchanged throughout his/her lifetime. In 13 th week of prenatal life the ridge formation occurs and in the 19th week of prenatal life the pattern formation is completed.The present study focused at understanding the knowledge and awareness level regarding dermatoglyphics to be used as a forensic tool among dental college students. Materials And Method An online survey was conducted with a self-structured questionnaire using an online survey platform google forms. The link was shared through social media. A total of 160 responses were received. The reactions recorded and were analyzed, and a statistical analysis chi-square test was performed. Result The result from this current survey depicts the awareness level of participants when they are asked about the name given to the examination of fingerprints 43.41% were answered as dactyloscopy, 37.21% were answered as entomology. The results were statistically significant according to the Chi-square test, where p< 0.05. Conclusion From this study, it is evident that the majority of them reported positively. The study concluded that most of them are aware of dermatoglyphics as a forensic tool in identification.